2011
DOI: 10.1002/chem.201003544
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Acid–Base Properties of Adenosine: The Intrinsic Basicities of N1, N3 and N7

Abstract: Adenosine (Ado) can accept three protons, at N1, N3, and N7, to give H(3) (Ado)(3+) , and thus has three macro acidity constants. Unfortunately, these constants do not reflect the real basicity of the N sites due to internal repulsions, for example, between (N1)H(+) and (N7)H(+). However, these macroconstants are still needed for the evaluations and the first two are taken from our own earlier work, that is, pK(H)(H(3))((Ado)) = -4.02 and pK(H)(H(2))((Ado)) = -1.53; the third one was re-measured as pK(H)(H)((A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 56 publications
3
82
0
Order By: Relevance
“…We found that twister does not have a HB donor with good geometry and a chemical group with a reasonable pK A to act as a general acid. The only HB donor with reasonable geometry is the N3 of A10, but this nitrogen has a very low pK A of about -4.2 to 1.0 (22,23). Although this would be a great chemical group to interact with the 5′-OH leaving group, it would require a highly perturbed pK A to act as a general acid.…”
Section: Discussionmentioning
confidence: 99%
“…We found that twister does not have a HB donor with good geometry and a chemical group with a reasonable pK A to act as a general acid. The only HB donor with reasonable geometry is the N3 of A10, but this nitrogen has a very low pK A of about -4.2 to 1.0 (22,23). Although this would be a great chemical group to interact with the 5′-OH leaving group, it would require a highly perturbed pK A to act as a general acid.…”
Section: Discussionmentioning
confidence: 99%
“…4.3 [31,35]), the (N1)H + sides 9 of adenosines (pK a ca. 3.8 [31,36]) as well as the (N7)H + of guanosines (pK a ca. 2.5 [31,37,38]),…”
Section: Insert Figure 2 Close To Here (Width: 6 Cm)mentioning
confidence: 99%
“…Note, the basicity, and thus the metal ion affinity, of N3 should not be underestimated: The micro acidity constant for the (N3)H + site in otherwise neutral adenosine was estimated as pk a/(N3)H = 1.5 ± 0.3 [36]; such a value is ideal for outersphere interactions [59][60][61], e.g., with Mg 2+ (see the discussed solid-state structure of Mg(2'AMP) in Section 3.2).…”
mentioning
confidence: 99%
“…In general, protonation occurs preferentially at N1 of adenine, with minor populations of protonation at N7 and N3. [29] It is one of our future aims to verify the precise location of protonation using the corresponding 15 N-single atom labeled A6. [30,31] In this context, we note that G48 (G62 in O. sativa twister ribozyme) has been suggested to act as general base and to activate the attacking 2′-OH.…”
mentioning
confidence: 99%